Survival of Salmonella enteric in skim milk powder with different water activity and water mobility. (January 2015) - Lian, Feng; Zhao, Wei; Yang, Rui-jin; Tang, Yali; Katiyo, Wendy
Abstract: Recently, the safety of low water activity ( a w ) foods started to become a major concern. It has been observed that microorganisms may not grow in low- a w foods but can survive for rather long periods of time, representing significant risk. Most researchers have been concentrating on the role of water activity. However, little is known about the effect of water mobility on influencing the survival of Salmonella in low- a w foods. In this study, water mobility of skim milk powder was manipulated using ultra-high pressure to change tertiary structure, thus changing water–protein interactions. Skim milk powder with different levels of water mobility at similar a w level were obtained to evaluate how a w and water mobility influenced the survival of Salmonella enteric in low- a w foods. Results showed that a w could influence the survival of S. enteric and the lower the a w, the higher the survival. Water mobility had little influence on the survival of S. enteric when a w was 0.33 and 0.53. However, it influenced its survival when a w was increased to 0.81. The survival population of S. enteric was higher in the sample with low water mobility. Highlights: Water mobility of skim milk powder was manipulated using ultra-high pressure. Effects of water activity on survival of Salmonella enteric in skim milk powder were investigated. Effects of water mobility on survival of S. enteric in skim milk powder were investigated.